Returns to routine job tasks in the German labour market: An instrumental variables approach - Emil Mihaylov (Tinbergen Institute, 2021)
This paper studies the impact of routine job tasks on workers wages in the German labour market. Using nationally representative data from the German Employment Survey, the paper finds that routine job tasks are negatively and significantly associated with workers hourly wages; the negative effect of routine tasks is most pronounced in high-skilled non-routine occupations where routine tasks are found to carry a substantial wage penalty. In order to account for the endogeneity of routine job tasks, the analysis employs an instrumental variable approach. The individual routine task-intensity of German workers in 2012 is instrumented with the routine task-intensity of the father's occupation in 1979 and the routine task-intensity of the workers' own occupation in 1979. The estimation procedure rests on the assumption that the two instruments are uncorrelated with the error term in the wage equation, conditional on a detailed set of individual, job, firm, industry and occupation-specific variables. Although the exogeneity of the instruments cannot be tested formally, the paper provides an extensive discussion of the instruments' validity and shows that the estimated negative effect is not sensitive to different model specifications, different definitions of the endogenous and instrumental variables, and different sample selection rules.
Keywords: J01; J24; J30; 330; job tasks; wages; instrumental variables; parents' occupation; Germany